Hubungan Self-Efficacy dengan Kecemasan Sosial pada Mahasiswa Perantauan di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Iega Nur Mawaddah (Fakultas Dakwah UIN KHAS Jember, 2022)
Anxiety is a state of worry, nervousness, or fear when facing difficult situations and believing that something bad will happen to oneself. Self-efficacy and social anxiety are two interrelated concepts, where a belief gained from previous experiences provides self-evaluation in facing social situations and performance. Anxiety is also experienced by international students at UIN KHAS Jember. Based on the results of a survey, anxiety is a problem for international students at UIN KHAS Jember. The research questions in this study are: first, how much self-efficacy do international students at UIN KHAS Jember have? Second, how much social anxiety do international students at UIN KHAS Jember have? Third, is there a relationship between self-efficacy and social anxiety in international students at UIN KHAS Jember? The research method used in this study is correlational research. The sampling technique used purposive random sampling with a total sample of 240 obtained from questionnaire data. Data validity and reliability were tested. The response to each instrument item was measured using a Likert scale. The analysis method used was normality test, linearity test, and Pearson correlation test. The first result shows that more international students at UIN KHAS Jember have moderate self-efficacy than those with low self-efficacy. Meanwhile, more international students with moderate social anxiety than those with low social anxiety. The third result shows a correlation coefficient of -0.259 with sig. 0.000 (p < 0.05), indicating a significant negative relationship between self-efficacy and social anxiety in international students at UIN KHAS Jember.